The influence leadership, communication, and training on risk management awareness / Siti Farhani Mat Husin - Mat Husin, Siti Farhani (2017)
This study examines the influence leadership, communication, and training on risk management awareness. In this study determines that most significant elements that contribute to risk management awareness. There are 100 questionnaire are distribute to the respondents. Data collected use in this research is Frequency analysis, Descriptive statistic, Reliability analysis, Pearson Correlation and multiple linear regressions. In this research, Pearson Correlation had shown that the leadership, communication, and training having the positive relationship with the risk management awareness. However, the multiple linear regression is used to predict the impact of independent variable on the dependent variable. In other words, it is to find out which one of the leadership, communication and training is the best predictors and influential to the risk management awareness. In conclusion, tangibility is most significant and more dominant in this research.